Financial Agglomeration and Transformation of Industrial Innovation Achievements - Guo, Yang (Transactions on Economics, Business and Management Research, 2024)
Finance stands as the lifeblood of the real economy, intricately interwoven with governmental factors (e.g., governance efficacy), levels of urbanization, and the reservoir of human capital. This study leverages panel data encompassing 30 provinces across China spanning from 2005 to 2020, with financial agglomeration (fin) as the focal variable. Employing the measurement framework , financial agglomeration is assessed via the location entropy of the financial sector derived from employee metrics. Subsequently, industrial structural evolution (str) is posited as the dependent variable, while governmental influences (zc), urbanization dynamics (cit1), and educational attainment (ledu) are incorporated as control variables to construct an empirical analysis model. The empirical findings, evaluated through Pool OLS, random effects, and fixed effects methodologies, corroborate a substantively positive correlation between financial agglomeration and industrial structural refinement.